Design Research: Past, Present and Future. (2nd January 2017) - Cooper, Rachel
Abstract: In the first of a series of invited papers to mark the 20th volume of the Design Journal, founding editor Rachel Cooper reflects on the changing landscape of design research activity since the journal's launch.